Draft Genomic Analysis of an Avian Multidrug Resistant Morganella morganii Isolate Carrying qnrD1 - Jones-Dias, Daniela; Clemente, Lurdes; Moura, Inês B.; Sampaio, Daniel A.; Albuquerque, Teresa; Vieira, Luís; Manageiro, Vera; Caniça, Manuela (Frontiers in Microbiology, 2016)
Morganella morganii is a commensal bacterium and opportunistic pathogen often present in the gut of humans and animals. We report the 4.3Mbp draft genome sequence of a M. morganii isolated in association with an Escherichia coli from broilers in Portugal that showed macroscopic lesions consistent with coliseptisemia. The analysis of the genome matched the multidrug resistance phenotype and enabled the identification of several clinically important and potentially mobile acquired antibiotic resistance genes, including the plasmid-mediated quinolone resistance determinant qnrD1. Mobile genetic elements, prophages and pathogenicity factors were also detected, improving our understanding towards this human and animal opportunistic pathogen.